2017
DOI: 10.1016/j.biopha.2017.05.101
|View full text |Cite
|
Sign up to set email alerts
|

Apocynin prevented inflammation and oxidative stress in carbon tetra chloride induced hepatic dysfunction in rats

Abstract: Apocynin prevented inflammation and oxidative stress in carbon tetrachloride induced hepatic dysfunction in rats http://researchonline.ljmu.ac.uk/6623/ Article LJMU has developed LJMU Research Online for users to access the research output of the University more effectively. Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Users may download and/or print one copy of any article(s) in LJMU Research Online to facilitate their private s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 32 publications
3
16
0
Order By: Relevance
“…Oxidative stress reportedly induces different hepatic diseases including liver cirrhosis, cancer, ischemia, reperfusion injury as well as drug/chemical mediated hepatic toxicity [24]. In the present study, TD peel extract combated oxidative stress, diminished inflammation and fibrosis in the liver tissues, and restored the function of the antioxidant enzymes against CCl 4 -provoked liver damage in rats.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Oxidative stress reportedly induces different hepatic diseases including liver cirrhosis, cancer, ischemia, reperfusion injury as well as drug/chemical mediated hepatic toxicity [24]. In the present study, TD peel extract combated oxidative stress, diminished inflammation and fibrosis in the liver tissues, and restored the function of the antioxidant enzymes against CCl 4 -provoked liver damage in rats.…”
Section: Discussionsupporting
confidence: 54%
“…A further deterioration in the hepatic antioxidant defense systems has been shown by the substantial decline in CAT and SOD activities in the CCl 4 -administered rats, the two major enzymes supporting the antioxidant protection system of body causing progression from steatosis to steatohepatitis [24]. It has been reported that reduction of CAT and SOD levels and increase in CYP2E1 activity occur together which stimulate the generation of various free radicals and reactive intermediates, thus making the liver more vulnerable to oxidative stress-induced damages [47].…”
Section: Discussionmentioning
confidence: 99%
“…4B and C). MDA is a lipid peroxidation product and is usually considered a reflection of cell injury (25). The present results showed that overexpressed miR-130a-3p or miR-301a-3p could ameliorate HG-induced MPC5 podocytes metabolic disturbance.…”
Section: Overexpressed Mir-130a-3p/301a-3p Inhibited Hg-induced Mpc5 supporting
confidence: 52%
“…Although, early antiviral therapy can reverse liver fibrosis in patients with HBV and HCV infection (D'Ambrosio et al, ; Marcellin et al, ), for other causes of liver fibrosis and cirrhosis, there are still no effective anti‐fibrosis drugs applied to clinical treatment (Sun & Kisseleva, ), Therefore, developing anti‐liver fibrosis drugs is highly significant (Lee, Wallace, & Friedman, ). We used fibrotic rats as research subjects, and apocynin (AP) (Rahman et al, ) as a positive control, and we observe the effect of UA intervention (UA prevention and treatment) on reversing liver fibrosis. Compared to the liver fibrosis group, the fibrous septum and collagen deposition were reduced in the liver tissue of the UA prevention and treatment group (Figure a–d).…”
Section: Discussionmentioning
confidence: 99%